Enhancing the Functionality of a Single Burner Electric Cooker through IoT Automation - Ilupeju, Akinola Mojeeb; Babalola, Abayomi Danlami; Temidayo, Oluyemi Tolulope (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
Single-burner electric cookers are frequently utilized in homes and small kitchens because they offer unmatched convenience and portability. However, they often grapple with challenges such as energy inefficiency and limited temperature control, and in some instances, pose potential hazards ranging from fires to electric shocks. Addressing these issues, this research explores the integration of IoT (Internet of Things) automation as a transformative solution to enhance the overall efficiency of single-burner electric cookers. Through the integration of IoT technology, the electric cooker was automated with programmable timer functionality and precise temperature control and connected to a smart device via a wireless connection. This allows users to remotely manage and control the cooker’s operations using a dedicated app. The system includes a microcontroller, temperature sensor, timer module, Wi-Fi module, and a mobile app. Users can input the desired cooking parameters on the app, which are then transmitted to the microcontroller through a Wi-Fi network. The temperature sensor continuously monitors the cooking temperature and sends feedback to the microcontroller, which makes necessary adjustments to maintain the desired temperature. The timer function ensures that the cooking process concludes at the specified time, preventing overcooking or burning of food. This system introduces features such as remote monitoring and control, improved cooking precision, enhanced safety measures, and increased energy efficiency